Postpartum State, but Not Maternal Caregiving or Level of Anxiety, Increases Medial Prefrontal Cortex GAD65 and vGAT in Female Rats - Ragan, Christina M.; Ahmed, Eman I.; Vitale, Erika M.; Linning-Duffy, Katrina; Miller-Smith, Stephanie M.; Maguire, Jamie; Lonstein, Joseph S. (Frontiers in Global Women's Health, 2022)
Upregulation of the inhibitory neurotransmitter, GABA, is involved in many of the behavioral differences between postpartum and nulliparous female rodents. This is evidenced by studies showing that pharmacological blockade of GABAergic activity impairs maternal caregiving and postpartum affective behaviors. However, the influence of motherhood on the capacity for GABA synthesis or release in the medial prefrontal cortex (mPFC; brain region involved in many social and affective behaviors) is not well-understood. Western blotting was used to compare postpartum and nulliparous rats in protein levels of the 65-kD isoform of glutamic acid decarboxylase (GAD65; synthesizes most GABA released from terminals) and vesicular GABA transporter (vGAT; accumulates GABA into synaptic vesicles for release) in the mPFC. We found that postpartum mothers had higher GAD65 and vGAT compared to virgins, but such differences were not found between maternally sensitized and non-sensitized virgins, indicating that reproduction rather than just the display of maternal caregiving is required. To test whether GAD65 and vGAT levels in the mPFC were more specifically related to anxiety-related behavior within postpartum mothers, we selected 8 low-anxiety and 8 high-anxiety dams based on their time spent in the open arms of an elevated plus maze on postpartum day 7. There were no significant differences between the anxiety groups in either GAD65 or vGAT levels. These data further indicate that frontal cortical GABA is affected by female reproduction and more likely contributes to differences in the display of socioemotional behaviors across, but not within, female reproductive state.